Extrapolating the financial position of the new Kufa Cement Factory for the period from 2005-2009 based on the financial analysis for the period from 1996-2004. An applied and predictive study. - Arshad A-jasim; Rdhi Sahab Abo Hamid (Iraqi Journal for Administrative Sciences, 2024)
Cement factories and their companies constitute the main and vital part of the industrial and economic activity in the country because they work to meet the basic needs of the individual, which leads to reducing the high rates of unemployment in that country and then increasing incomes by improving the living and social conditions of its individuals in a way that ensures an increase in their stability. In addition, these factories contribute To diversifying the economy and saving foreign currencies. The previous years of the new Kufa Cement Factory, since its establishment on June 20, 1995, witnessed support for the national economy in a way that led to it gaining a foothold in the market among Arab and international competing companies because of the product it provides with specifications that fall within the framework of comprehensive quality that carries within it a philosophy and tools. An administrative focus on continuous improvement in various aspects of activities and relationships inside and outside the factory to achieve customer satisfaction and ensure the factory’s continuity in front of its competitors in the business environment.